Новый гуманизм: «Метафора раны» в романе К. Исигуро «Не отпускай меня» - Бондаренко, Л.В.; Фридрикова, Д.М. (Культура народов Причерноморья, 2013)
В статье рассматривается гуманистический аспект современного постмодернистского
романа на материале романа британского писателя японского происхождения Кацуо Исигуро «Не
отпускай меня». Приходим к заключению, что в современном романе главным лейтмотивом становятся
гуманистические проблемы общества, обретающее свое художественное выражение в виде
неизлечимой раны в трагических воспоминаниях героев, «метафоры раны», неизбывной боли. В
исследовании используется культурно-исторический поход при анализе гуманистического аспекта в
тексте, метод перцепции, внимательного прочтения, а также психологический поход.
Ключевые слова: новый гуманизм, метафора раны, современный постмодернистский роман,
двойничество. Стаття присвячена досліжденню гуманістичного аспекту у сучасному постмодерністскому
романі на матеріалі романа Кацуо Ісігуро “Не відпускай мене”. Ці та інші художні експлікації нового
гуманізму знаходять яскраве вираження у романі К. Ісігуро “Не відпускай мене”. У дослідженні
використовуються культурно-історичний підхід у аналізі гуманізму у тексті, метод перцепції,
уважного читання та психологічний підхід.
Ключові слова: новий гуманізм, метафора рани, сучасний постмодерністський роман, двойнічество. The article is devoted to the study of the humanistic aspect in the present day novel, which remains
postmodern in form but tends to develop a new content. Humanistic and hermeneutic approaches are applied in
the analysis referring to an article of Olga Gumajlo. It focuses on personal and social problems of the 21st
century individuals. The leading theme finds its artistic explication in the image of “uncured wound” in the
tragic reminiscences of the characters, “metaphor of wound” and insatiable pain. These and other artistic
explications of the new humanism are widely found in Kazuo Ishiguro literary works, as his name entered
modern literature with his “metaphor of wound” which is the main theme in his novel “Never Let Me Go” and
others. It follows that it is not possible to escape suffering and appease the pain, so the only way to survive, is to
accept it. The tragedy of the modern society is that it is killing itself by all kinds of sophisticated means and
nothing could be done about that so far. Cultural-historical approach is applied in the research to analyze
humanistic aspect in the text, method of perception, method of close reading, and psychological approach.
Key words: new humanism, “metaphor of wound”, postmodern novel, binary oppositions.